2021
DOI: 10.3390/ijerph18136878
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluoride Adsorption Mechanism and Capacity of Different Types of Bone Char

Abstract: The fluoride adsorption capacity of three types of bone char (BC), including cow BC (CBC), chicken BC (CKBC), and pig BC (PBC), was examined. At the optimum charring conditions (temperature and time), PBC had the highest hydroxyapatite (HAP) content (0.928 g-HAP/g-BC), while CBC had the highest specific surface area (103.11 m2/g-BC). CBC also had the maximum fluoride adsorption capacity (0.788 mg-F/g-HAP), suggesting that fluoride adsorption capacity depends more on the specific surface area of the BC than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 82 Dehydroxylation of hydroxyapatite component of bone char due to charring at high temperatures greater 500 °C decreases adsorption capacity, especially for anion pollutants such as fluorine and phosphorus. 83 Recently, Azeem et al 28 published a detailed review outlining the key benefits of using bone waste to produce bone char as well as bone-derived biochar, utilizing them as low-cost and effective methods for excluding potentially toxic elements (such as As, Cd, Cr, Cu, Ni, Pb, Hg, Sb, Se, V, and Zn) from contaminated water and soils. It has also been shown that the adsorption capacity of bone char closely correlates with the characteristics of its pores for metallic or cationic pollutants.…”
Section: Applications Of Bone Derived Materialsmentioning
confidence: 99%
“… 82 Dehydroxylation of hydroxyapatite component of bone char due to charring at high temperatures greater 500 °C decreases adsorption capacity, especially for anion pollutants such as fluorine and phosphorus. 83 Recently, Azeem et al 28 published a detailed review outlining the key benefits of using bone waste to produce bone char as well as bone-derived biochar, utilizing them as low-cost and effective methods for excluding potentially toxic elements (such as As, Cd, Cr, Cu, Ni, Pb, Hg, Sb, Se, V, and Zn) from contaminated water and soils. It has also been shown that the adsorption capacity of bone char closely correlates with the characteristics of its pores for metallic or cationic pollutants.…”
Section: Applications Of Bone Derived Materialsmentioning
confidence: 99%
“…It is necessary to have both an awareness of fluoride’s dispersion and a comprehensive grasp of its many probable sources and especially removal technologies for management to be effective. Various water and groundwater treatment technologies have been applied to remove fluoride from water sources, such as electrodialysis [ 7 , 8 ], membrane filtration [ 9 , 10 , 11 ], and adsorption processes [ 12 , 13 , 14 , 15 , 16 ]. Of these technologies, when applied in a local community, adsorption is considered an excellent choice for defluorination due to its low cost, ease of design and operation, and high level of effectiveness [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the solution pH is less than the pHpzc of the adsorbent, the surface of an adsorbent becomes positively charged attracting more fluoride ions but when the solution pH is more than the pHpzc of the adsorbent, its surface becomes negatively charged repulsing the fluoride ions. Therefore, defluoridation is low when the initial pH is close to or higher than the adsorbent pHpzc due to proton release (deprotonation) (Sawangjang et al, 2021).…”
Section: Soil Propertiesmentioning
confidence: 99%